Operational value creation in private equity secondary buyouts : Evidence from the Nordics - Kilpeläinen, Erkka (My University, 2022)
During the 21st century, secondary buyouts (SBOs) have increased in popularity as an exit method for private equity buyout investments. Secondary buyout refers to a situation where a buyout investor sells their portfolio company to another financial buyer, contrary to primary buyouts, where the target company is acquired by a buyout investor for the first time. Historically, buyout funds have mostly chosen to exit their investments via initial public offerings (IPOs) or selling the portfolio company to a strategic acquirer. The surge of popularity in SBOs as an exit method has raised questions regarding the rationale of such transactions. The goal of this thesis is to examine the differences in operational value creation between secondary and primary buyouts in the Nordic region. In the past, SBOs have been seen as transactions that do not offer similar operational value creation potential compared to first-time leveraged buyouts. The main drivers for SBOs have been assumed to be external, mainly related to debt market conditions, as well as pressure for the participants to engage in acquisitions or exits due to reputational reasons or fund life cycle considerations. Furthermore, the assumption has been that in terms of operational value creation, there is not much that the secondary buyer can achieve because the initial buyer has already realized all the low-hanging fruit in the portfolio company. The empirical part of the thesis uses a dataset of leveraged buyouts done by Nordic-based buyout funds between 2012 and 2019. Operational value creation is measured as the development of selected key operational metrics of the target company, related to growth and profitability of the company. The used operational metrics are revenue growth, growth in earnings before interest, taxes, depreciation, and amortization (EBITDA), changes in EBITDA margin, as well as changes in return on assets (RoA). The analysis uses statistical methods to compare the development of the selected operational metrics in secondary buyouts to primary buyouts. The results of the thesis do not indicate that there is any significant difference between the selected operational metrics of secondary buyout targets, compared to primary buyout targets. This study therefore presents that secondary buyouts have a similar operational value creation profile to primary buyouts, suggesting that secondary buyouts should not be seen as “second-tier” deals for the acquirers. The results add to the limited number of existing secondary buyout literature covering the Nordic region.
Keywords: Private equity, buyout, operational performance, secondary buyout